Taxonomic re-evaluation of the wolf spider Wadicosa okinawensis (Tanaka, 1985) through morphological examination and dna barcoding, with its redescription and a new synonymy (Araneae, Lycosidae, Pardosinae) - Thapa Magar, Kiran; Ballarin, Francesco; Eguchi, Katsuyuki (Academia Journal of Biology, 2025)
The genus Wadicosa Zyuzin, 1985 comprises medium-sized, free-hunting wolf spiders characterized by an anterior retrolateral process on the male palpal tegulum and rounded or oval foveolae in the female epigyne. Among its 19 valid species, Wadicosa okinawensis (Tanaka, 1985) has limited diagnostic information on its genital structures and inadequate illustrations for identification. This study addresses these gaps providing a thorough redescription of W. okinawensis and detailed photographs of its diagnostic characters based on specimens from its type locality and surrounding areas. A comparative morphological analysis of W. okinawensis and Wadicosa daliensis Yin, Peng & Zhang, 1997 from China and Laos reveals no significant morphological differences between the two species. Consequently, we propose W. daliensis as a junior synonym of W. okinawensis. For the first time, W. okinawensis is included in DNA barcoding which supports its separation from the morphologically similar Wadicosa fidelis (O. Pickard-Cambridge, 1872). This work enhances the taxonomy of Wadicosa, facilitating species identification and serving as a valuable reference for understanding the diversity of the family Lycosidae.